Impact of phosphate availability and nutritional status on the wheat transcriptome - Grün, Astrid (2015)
Economic, political and environmental factors have prioritized the need for research on phosphate (Pi) acquisition efficiency (PAE), Pi use efficiency (PUE) and Pi fertilizer uptake efficiency in crops. However, the coordination of molecular responses to Pi starvation and the mechanisms of Pi starvation tolerance have been investigated predominantly in model plants but remain elusive in grain crops, especially in wheat. This project investigates transcriptional profiles in wheat, particularly in the roots, as a response to nutrient availability focusing on phosphate (Pi). Furthermore, appropriate screening approaches and the difficulties in crop improvement, particularly for wheat, are discussed. Pi acquisition by plants is mediated by members of Pi transporter families. The roles of these Pi transporters in Pi partitioning and re-translocation is complex and the knowledge about their functioning in wheat still limited. Here, members of the Pht1 family in wheat were identified, their expression profiles determined when exposed to different nutrient regimes in roots and ear tissues at various developmental stages and their potential role as targets for genetic improvement discussed. In addition to Pi transporters, regulatory genes including transcription factors, signalling pathways and apparently other Pi-responsive genes with unknown function are also of critical importance. Therefore, the genome-wide responses to limited nutrient availability were investigated for the first time in roots of field-grown wheat exposed to limited nutrient availability resulting in the identification of several candidate genes for PAE/PUE improvement on the molecular level. These data were validated against other studies and across a wider wheat germplasm. Furthermore, the correlation of candidate gene expression to the nutritional status, Pi availability and PAE/PUE properties revealed four potential target genes which may be major contributors to genotypic diversity of this trait. However, there are still some agronomic bottlenecks which impede implementing Pi efficient crops and the application of molecular tools and marker genes.